CANADA'S COMMUNITY COLLEGES: A CRITICAL ANALYSIS (Authors: John D. Dennison and Paul Gallagher) - Gordon, Robert A. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1987)
John D. Dennison and Paul Gallagher. CANADA'S COMMUNITY COLLEGES: A CRITICAL ANALYSIS. Vancouver, BC: University of British Columbia Press, 1986. 370 pp. $16.95.